Consumer Protection in Live Shopping Transactions of Thrift Products on TikTok - Siti Syarifah Wafiqah Wardah; Yusi Irensi Seppa; Syarifuddin Syarifuddin (Public Resource Innovation Management and Excellence, 2026)
This study is grounded in consumer protection theory and the concept of asymmetric information in digital transactions, which explain the imbalance of information and bargaining power between business actors and consumers in electronic commerce. The research aims to analyze consumer protection in live shopping transactions of thrift products on TikTok, identify potential risks and violations of consumer rights, and examine business actors’ legal responsibility and dispute resolution mechanisms under Indonesian law. This study employs a normative juridical approach through library research and document analysis of primary legal materials, including the Consumer Protection Law, the Electronic Information and Transactions Law, and regulations on electronic commerce, supported by relevant scholarly literature. Data were analyzed using qualitative normative analysis by interpreting legal provisions and relating them to the characteristics of live shopping practices. The results show that although the legal framework is comprehensive, the real-time and persuasive nature of live shopping increases the risk of information asymmetry, product misrepresentation, unilateral no-refund policies, and evidentiary difficulties. The novelty of this research lies in its specific focus on live shopping thrift transactions as a digital trade model that heightens consumer vulnerability.